Evaluation of the effect of brief online therapy during the COVID-19 pandemic (Research, Society and Development, 2022)
Given the negative impacts of the COVID-19 pandemic on the population's mental health, scientific research that evaluates the effectiveness of psychological support services has become relevant. This study assessed the effect of brief online therapy on participants assisted by the extension project "Psychological Support – COVID19" . The procedure consisted of offering one to four sessions of brief online therapy to participants of both sexes, aged between 20 and 70. Participants were health professionals, infected people or their relatives, and professionals from other areas, such as police staff and teachers. The Outcome Questionnaire (OQ-45) and the Hospital Anxiety and Depression Scale (HADS) were applied in three stages: pre-intervention, post-intervention, and follow-up (average of 2 months after post-intervention). Participants reported lower anxiety (HADS) and "subjective discomfort" (OQ45), but the effect on depression (HADS) and on "interpersonal relationships", and "social role performance" (OQ45) was not significant. We concluded that the psychological support offered by the Project effectively reduced anxiety and subjective discomfort. Also, free, and accessible services to the population are necessary for crises since the psychological effects of the COVID-19 pandemic affected health professionals and the general population.